The influence of airbrush drawing on children's artistic abilities at Lukmanul Hakim Sungai Penuh kindergarten - Adha, Asty E Febri; Mayar, Farida (Universitas Islam Negeri Raden Intan Lampung, 2024)
Background: Low levels of artistic ability (drawing) in early childhood are the background for conducting this research, as there are currently no techniques provided by teachers during drawing activities, leading to boredom among children which affects their low level of artistic ability (drawing). Aim: The aim of this research is to identify the extent of the impact of airbrush drawing activities on the artistic abilities of children at Lukmanul Hakim Sungai Penuh Kindergarten. Method: The methodology used in this research is a quantitative quasi-experimental approach. Data collection techniques involved performance tests and documentation. Results: Data analysis included tests for normality, homogeneity, and hypothesis testing. Based on the t-test calculation using SPSS version 23, a Sig value (2-tailed) of 0.01 < 0.05 was obtained.Conclusion: Thus, it is concluded that there is an influence of airbrush drawing activities on the artistic abilities of early childhood children.